Dual‐composite drag‐reduction surface based on the multilayered structure and mechanical properties of tuna skin. Issue 8 (5th March 2021) - Chen, Dengke; Cui, Xianxian; Chen, Huawei
Abstract: Energy efficiency and friction reduction have attracted considerable research attention. To design low drag surfaces, researchers derived inspiration from nature on various types of drag reduction methods with exceptional functional surfaces, such as fish skin that possesses low friction. Fishes with high‐performance swimming possess a range of physiological and mechanical adaptations that are of considerable interest to physiologists, ecologists, and engineers. Although tuna is a fast‐swimming ocean‐based predator, most people focus their attention on its nutritional value. In this study, the multilayered structures and mechanical properties of tuna skin are first analyzed, and then the drag‐reduction effect of the bionic fish‐scale and dual‐composite surfaces are studied based on the computational fluid dynamics method. The results indicate that tuna skin is composed of five layers, with the fish scale covered by a flexible epidermis layer. According to the uniaxial tension results, the modulus and tensile strength of the epidermis are obtained as 1.17 and 20 MPa, respectively. The nanoindentation results show that the modulus and hardness of the outer surface of the fish scale are larger than that of the inner surface, while those of the dry state are larger than those of the hydrated state. The simulation results show that both the bionic fish‐scale and dual‐composite surfaces display drag reduction, with the maximum drag‐reduction rate of 25.7% achieved by the bionic dual‐composite surface. These findings can offer a reference for in‐depth performance analysis of the hydrodynamics of tuna and provide new sources of inspiration for drag reduction and antifouling. Abstract : The multilayered structure of the tuna skin was researched by the anatomy experiment and microscopy technology. The mechanical properties of the epidermis and fish scale layer were analyzed by using a tensile machine and nanoindentation, respectively. The dual‐composite structure of tuna skin has good drag reduction effect. There was a composite phenomenon to explain the drag reduction property.